Feasibility and acceptability of gamified cycling exercise for residents in a long-term care home: A qualitative study - Lillian Hung; Zhiqi Shen; Joey Cheung; Michelle Lam; Jamie Lam; Tiffany Wu; Rikki Wu; Arwen Fong; Michelle Xiao; Riea Singh; Yang Qiu; Lily Wong; et al. (PLoS ONE, 2025)
Gamification can motivate older adults to exercise by transforming physical activities into enjoyable experiences. Incorporating gaming elements in cycling exercises can foster a sense of interest and achievement, potentially improving health outcomes. This study investigated the acceptability and feasibility of motivating residents living in a long-term care (LTC) home with a gamified cycling exercise. Fourteen residents completed a 4-week gamified cycling exercise twice a week. Safety during exercise was addressed by assessing heart rate and observation. With an interpretive description approach, we conducted observations and interviews with residents and family members and focus groups with staff and leadership. The thematic analysis identifies three themes representing the feasibility and acceptability of gamified cycling exercise among LTC residents: ease of use and accessibility, physical and mental health benefits, fun engagement and community building. Future research should explore dementia-friendly design, culture-related game content, family orientation and engagement, group exercise and organization support. This study showed the promising acceptability and feasibility of gamified cycling exercise in an LTC home. Successful implementation relies on tailoring interventions to meet residents’ specific needs and preferences while acquiring rapport with interdisciplinary staff in the care home.